METHOD FOR MODIFYING PROFILE OF CYCLOIDAL WHEEL CONSIDERING COMPENSATION FOR ELASTIC DEFORMATION - QIN ZhengZheng; WANG Quan; ZHAO DaXing; WANG Jun; ZENG LiLei (Jixie qiangdu)
Considering the influence of elastic deformation on the profile of the cycloid,a cycloid profile modification method for compensating elastic deformation is proposed.Based on the theory of cycloid profile modification,the coordinates of the meshing point of the cycloid were obtained. The coordinate transformation principle was used to fit the profile of the cycloid after elastic deformation,and the theoretical calculation of the contact force of the cycloid tooth surface was carried out. And the mathematical model of the profile modification of the cycloid with elastic deformation characteristics was established,which was solved by genetic algorithm and compared with the modification method without considering elastic deformation.The results show that compared with the modification method without considering elastic deformation,the fitting degree of the actual working tooth profile and the angle modification tooth profile is improved to 1. 52 times,and the contact force of the tooth surface is reduced to8. 27%,thus verifying the rationality and feasibility of the method.